Intracranial Hypertension and Cerebral Hypoperfusion in Children With Severe Traumatic Brain Injury: Thresholds and Burden in Accidental and Abusive Insults. Issue 5 (May 2016) - Miller Ferguson, Nikki; Shein, Steven L.; Kochanek, Patrick M.; Luther, Jim; Wisniewski, Stephen R.; Clark, Robert S. B.; Tyler-Kabara, Elizabeth C.; Adelson, P. David; Bell, Michael J.
Abstract : Objectives: The evidence to guide therapy in pediatric traumatic brain injury is lacking, including insight into the intracranial pressure/cerebral perfusion pressure thresholds in abusive head trauma. We examined intracranial pressure/cerebral perfusion pressure thresholds and indices of intracranial pressure and cerebral perfusion pressure burden in relationship with outcome in severe traumatic brain injury and in accidental and abusive head trauma cohorts. Design: A prospective observational study. Setting: PICU in a tertiary children's hospital. Patients: Children less than18 years old admitted to a PICU with severe traumatic brain injury and who had intracranial pressure monitoring. Interventions: None. Measurements and Main Results: A pediatric traumatic brain injury database was interrogated with 85 patients (18 abusive head trauma) enrolled. Hourly intracranial pressure and cerebral perfusion pressure (in mm Hg) were collated and compared with various thresholds. C -statistics for intracranial pressure and cerebral perfusion pressure data in the entire population were determined. Intracranial hypertension and cerebral hypoperfusion indices were formulated based on the number of hours with intracranial pressure more than 20 mm Hg and cerebral perfusion pressure less than 50 mm Hg, respectively. A secondary analysis was performed on accidental and abusive head trauma cohorts. All of these were compared with dichotomized 6-month Glasgow Outcome Scale scores. The models with the number of hours with intracranial pressure more than 20 mm Hg ( C = 0.641; 95% CI, 0.523–0.762) and cerebral perfusion pressure less than 45 mm Hg ( C = 0.702; 95% CI, 0.586–0.805) had the best fits to discriminate outcome. Two factors were independently associated with a poor outcome, the number of hours with intracranial pressure more than 20 mm Hg and abusive head trauma (odds ratio = 5.101; 95% CI, 1.571–16.563). As the number of hours with intracranial pressure more than 20 mm Hg increases by 1, the odds of a poor outcome increased by 4.6% (odds ratio = 1.046; 95% CI, 1.012–1.082). Thresholds did not differ between accidental versus abusive head trauma. The intracranial hypertension and cerebral hypoperfusion indices were both associated with outcomes. Conclusions: The duration of hours of intracranial pressure more than 20 mm Hg and cerebral perfusion pressure less than 45 mm Hg best discriminated poor outcome. As the number of hours with intracranial pressure more than 20 mm Hg increases by 1, the odds of a poor outcome increased by 4.6%. Although abusive head trauma was strongly associated with unfavorable outcome, intracranial pressure/cerebral perfusion pressure thresholds did not differ between accidental and abusive head trauma.